2017
DOI: 10.2196/mhealth.7311
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for Sustained Use of an Activity Tracker: Observational Study

Abstract: BackgroundA lack of physical activity is considered to cause 6% of deaths globally. Feedback from wearables such as activity trackers has the potential to encourage daily physical activity. To date, little research is available on the natural development of adherence to activity trackers or on potential factors that predict which users manage to keep using their activity tracker during the first year (and thereby increasing the chance of healthy behavior change) and which users discontinue using their trackers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
100
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(123 citation statements)
references
References 71 publications
17
100
2
1
Order By: Relevance
“…Mercer et al and Rosenberg et al both suggested that usability could be improved by having more compatible computers and smartphones, comprehensive paper manuals, and apps that interpret the user data. Studies among the elderly and adults [15][16][17][18][19][20][21][22][23][24][25][26][27][28] showed considerable similarities with the results of this study and those of Mercer et al and Rosenberg et al Older people and adults accepted the activity tracker, found them stimulating, increased awareness, and experienced them as useful. However, especially elderly stated they would prefer an activity tracker which is easier to use and adapted to their needs and skills.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Mercer et al and Rosenberg et al both suggested that usability could be improved by having more compatible computers and smartphones, comprehensive paper manuals, and apps that interpret the user data. Studies among the elderly and adults [15][16][17][18][19][20][21][22][23][24][25][26][27][28] showed considerable similarities with the results of this study and those of Mercer et al and Rosenberg et al Older people and adults accepted the activity tracker, found them stimulating, increased awareness, and experienced them as useful. However, especially elderly stated they would prefer an activity tracker which is easier to use and adapted to their needs and skills.…”
Section: Discussionsupporting
confidence: 81%
“…Feasibility aspects such as user-friendliness and sustained use of activity trackers have been studied in healthy adults [15][16][17][18][19][20][21][22] and the elderly [23][24][25][26][27][28]. From these studies it appears that in general, healthy adults and the elderly are open and positive towards the use of activity trackers.…”
Section: Introductionmentioning
confidence: 99%
“…Recent quantitative research more broadly identified factors (e.g., perceived usefulness) associated with engagement. 44,45 Our qualitative work uncovered nuances within each factor, such as how previously unidentified variations in the depth of insights obtained from the data influenced how engaged and unengaged patients perceived usefulness. Such nuances may be testable in future quantitative studies in this population, using a larger sample size.…”
Section: Relationship To Prior Workmentioning
confidence: 95%
“…The use of technologies in lifestyle interventions, such as webs, mobile applications, or physical activity trackers, has shown similar trends, with adherence rates tending to decline at 2 to 3 months of follow-up. 9 ' 16 ' 17 The TI group shows similar preliminary results for weight loss and control of obesity comorbidities when compared to usual care. At the completion of the ongoing clinical trial, these results will be reevaluated to assess the potential role of web support for weight-loss maintenance as well as its costeffectiveness.…”
Section: Discussionmentioning
confidence: 80%